The Risk of Crimean Congo Haemorrhagic Fever in India as a Growing Health Concern - Garg, Gurisha; Garg, Sonakshi; Kamal, Raj; Kurmi, Balak D.; Singh, Amandeep (Infectious Disorders - Drug Targets, 2024)
Every year witnesses an outbreak of some or the other zoonotic disease that causes the unparalled loss of human life. The year 2022 presented the outbreak of Crimean Congo haemorrhagic fever (CCHF), which brought unprecedented challenges to individuals as well as to the healthcare system all around the world, making it a serious health concern. Rising health concerns have highlighted the importance of managing and decreasing the further transmission of the CCHF virus. CCHF is one of tick-borne viral diseases, which spreads due to various reasons like changes in global warming, environmental influences, and other ecological factors. All these factors somehow impact the disease prevalence. This disease has a negative impact on both humans and livestock. The diverse climate and significant livestock population of India make it susceptible to the prevalence of CCHF. Therefore, it is the need of the hour to develop some strategies in order to tackle the challenges posed by CCHF. This article includes all the cases of CCHF that have occurred in India from the year 2011, along with the fatality rates associated with this disease. Also this study discusses the need to explore some specific drugs for the management and prevention of such diseases. In addition, the pathogenesis of the disease progression, along with some protective measures suggested by the government has been described for prevention of CCHF. Subsequently, this article attempted to draw attention towards the risk that may be posed by CCHF in the coming scenario, emphasizing the importance of taking proactive measures in anticipation of such risks.
Keywords: CCHF